2021
DOI: 10.1093/abbs/gmab010
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 beta-induced chloride currents are important in osteoarthritis onset: an in vitro study

Abstract: Persistent hypotonic and inflammatory conditions in the joint cavity can lead to the loss of cartilage matrix and cell death, which are the important mechanisms of osteoarthritis (OA) onset. Previous studies have confirmed that the existence of a hypotonic environment is a red flag for inflammation, as hypotonic environment induces the opening of the chloride channel of the cell and promotes chloride ion efflux, which prompts the cell volume to increase. Chloride channels play an important role in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Many inflammatory factors such as interleukin-1β (IL-1β) and tumor necrosis factor alpha (TNF-α) upregulate the expression of MMP-13, which in turn triggers an increase in matrix catabolism, disrupts the balance between cartilage matrix synthesis and catabolism, and leads to cartilage degenerative diseases, such as OA. We recently confirmed that increased expression of COL I, decreased expression of COL II, a disordered cytoskeletal protein distribution, and loss of cell membrane integrity are important characteristics of OA, indicative of a decrease of anabolism of human OA chondrocytes [ 7 ]. We also confirmed that high expression of MAPK-14 may promote chondrocyte death [ 8 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 86%
“…Many inflammatory factors such as interleukin-1β (IL-1β) and tumor necrosis factor alpha (TNF-α) upregulate the expression of MMP-13, which in turn triggers an increase in matrix catabolism, disrupts the balance between cartilage matrix synthesis and catabolism, and leads to cartilage degenerative diseases, such as OA. We recently confirmed that increased expression of COL I, decreased expression of COL II, a disordered cytoskeletal protein distribution, and loss of cell membrane integrity are important characteristics of OA, indicative of a decrease of anabolism of human OA chondrocytes [ 7 ]. We also confirmed that high expression of MAPK-14 may promote chondrocyte death [ 8 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 86%
“… 32–35 Studies have shown that artificially reducing the osmotic pressure of the extracellular fluid induces cell swelling, which activates the release of caspase-1 and the inflammatory factor IL-1β through the NLRP3 inflammasome, and then triggers a series of cellular inflammatory reactions, and a large number of activated inflammatory factors will eventually lead to inflammatory cell death. 36 , 37 These pathophysiological processes are related to the abnormal increase in cell volume mediated by the abnormal activation of cell chloride ion channels. One previous study showed a functional deactivation and disordered distribution of LRRC8A chloride channels in OA chondrocytes, 37 which we believe may be a new and valuable research direction.…”
Section: Extracellular Microenvironment and The Pathogenesis Of Oamentioning
confidence: 99%
“… 36 , 37 These pathophysiological processes are related to the abnormal increase in cell volume mediated by the abnormal activation of cell chloride ion channels. One previous study showed a functional deactivation and disordered distribution of LRRC8A chloride channels in OA chondrocytes, 37 which we believe may be a new and valuable research direction.…”
Section: Extracellular Microenvironment and The Pathogenesis Of Oamentioning
confidence: 99%
See 2 more Smart Citations